2020
DOI: 10.1039/d0ra01835j
|View full text |Cite
|
Sign up to set email alerts
|

Insight into anomalous hydrogen adsorption on rare earth metal decorated on 2-dimensional hexagonal boron nitride: a density functional theory study

Abstract: The central rare earth cerium atom and underlying apolar B–N bonds in two-dimensional hexagonal boron nitride facilitate a unique arrangement of hydrogen molecules which leads to fairly strong adsorption of eight hydrogen molecules per metal atom.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 66 publications
0
3
0
Order By: Relevance
“…It is reported that h-BN doped with cerium metal can significantly increase hydrogen adsorption energy than pristine h-BN. [90] Jia-Xin king et al [91] used DFT to calculate hydrogen storage capacity on the pure h-BN. However, hydrogen adsorption energy on the pure h-BN was found by considering more favorable adsorption site (Refer Table 3).…”
Section: Hexagonal Boron Nitride As the Hydrogen Storagementioning
confidence: 99%
See 1 more Smart Citation
“…It is reported that h-BN doped with cerium metal can significantly increase hydrogen adsorption energy than pristine h-BN. [90] Jia-Xin king et al [91] used DFT to calculate hydrogen storage capacity on the pure h-BN. However, hydrogen adsorption energy on the pure h-BN was found by considering more favorable adsorption site (Refer Table 3).…”
Section: Hexagonal Boron Nitride As the Hydrogen Storagementioning
confidence: 99%
“…It is reported that h‐BN doped with cerium metal can significantly increase hydrogen adsorption energy than pristine h‐BN. [ 90 ]…”
Section: Hexagonal Boron Nitride As the Hydrogen Storagementioning
confidence: 99%
“…Structurally analogous to graphene is hexagonal boron nitride (h-BN), a van der Waals 2D material with outstanding properties such as chemical inertness, a high thermal stability, low density, excellent mechanical strength, and a wide tunable band gap of ∼5.9 eV. , Previous studies have suggested plausible expansion of the applications of h-BN by tuning its geometrical structure and spin state through adsorption or doping with other TM atoms. Moreover, unlike graphene, the structure of h-BN is composed of heteroatomic elements nitrogen (N) and boron (B), each with different electron distribution, suggesting stronger interaction with transition metals due to its polar nature. TM adsorption site occupancy on h-BN monolayer has triggered further research interest since theoretical work has revealed that hybridization between N and B with individual TM can induce different electronic characteristics . Although numerous studies have been published on TM/graphene interactions, limited information is available on TM/h-BN interactions.…”
mentioning
confidence: 99%